Role of LptD in Resistance to Glutaraldehyde and Pathogenicity in Riemerella anatipestifer - Huang, Li; Wang, Mingshu; Mo, Ting; Liu, Mafeng; Biville, Francis; Zhu, Dekang; Jia, Renyong; Chen, Shun; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; et al. (Frontiers in Microbiology, 2019)
Riemerella anatipestifer (R. anatipestifer, RA) is a multidrug-resistant, gram-negative bacterium that causes disease in ducks and other birds. Despite being an important pathogen in the poultry industry, the pathogenesis and drug resistance mechanisms of this bacterium are poorly understood. An analysis of our unpublished RNA-Seq data showed that lptD is transcribed at higher levels in RA CH-1 strain than in RA ATCC11845 strain. In addition, RA CH-1 has been shown to display more extensive drug resistance than RA ATCC11845. Since LptD is involved in LPS biogenesis and drug resistance, we wondered if lptD is associated with increased R. anatipestifer resistance to glutaraldehyde, a disinfectant used in the poultry industry. In this study, the MIC of glutaraldehyde for RA CH-1 was determined to be 0.125%, whereas an MIC of 0.05% was observed for RA ATCC11845. Furthermore, the level of lptD transcription in RA CH-1 was consistently 2-fold higher than that observed in RA ATCC11845. Moreover, lptD transcription was upregulated in both strains at a subinhibitory concentration of glutaraldehyde. The role of lptD in R. anatipestifer was further assessed by constructing an RA ATCC11845 strain with low lptD expression, RA ATCC11845 lptD-. The growth of RA ATCC11845 lptD- was severely impaired, and this strain was more sensitive than the wild-type strain to glutaraldehyde. Moreover, compared to the wild-type strain, RA ATCC11845 lptD- exhibited decreased biofilm formation and was more sensitive to duck serum. Finally, low lptD expression led to decreased colonization in ducklings. These results suggest that lptD is involved in R. anatipestifer glutaraldehyde resistance and pathogenicity.